The Children's book of Islam. - Ahsan, M. M (Islamic Foundation, 1993)
Foundamental passages and tenants of Islam for beginners, followed by a "workbook" of questions
Ibadah (Worship in Islam)
Keywords: Islam; Islamic religious education of children